STRATEGI PENANGGULANGAN KENAKALAN PESERTA DIDIK DI SMP NEGERI 1 BUA PONRANG KEC. PONRANG KAB. LUWU - Andi Kasmawati; Muhammad Sudirman; Al Fitrianti Iwan (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2024)
This research aims to determine: (1) Forms of student delinquency at SMP Negeri 1 Bua Ponrang. (2) Factors that cause student delinquency at SMP Negeri 1 Bua Ponrang. (3) Strategies used by teachers in dealing with student delinquency at SMP Negeri 1 Bua Ponrang. This research is qualitative research with a qualitative descriptive approach, the types of data used in the research are primary data and secondary data. Data collection techniques were obtained through observation, interviews, and documentation. The data analysis used is data reduction, data presentation, and drawing conclusions. The results of the research show that: (1) Forms of student delinquency at SMP Negeri 1 Bua Ponrang (a) minor or ordinary delinquency, namely not doing assignments, behaving and speaking impolitely, playing truant and smoking. (b) mischief which leads to violations and crimes, namely fighting and shouting. (2) Factors causing student delinquency at SMP Negeri 1 Bua Ponrang (a) self-factors (internal), namely weak self-control and lack of understanding of religious values. (b) family, school and community factors (external). External factors (family environment) include family disharmony and broken homes (family disintegration), lack of attention and affection from parents, and economic limitations which cause difficulties in meeting children's needs. External factors (school environment) include students' interactions with peers who are less supportive. External factors (community environment) are the environment where students live which is less conducive, children live in an environment that is criminal and full of violence. (3) Strategies used by teachers in dealing with student delinquency at SMP Negeri 1 Bua Ponrang (a) preventive strategies, namely explaining school rules and regulations during MPLS, as a model or role model, building positive relationships and strengthening cooperation between schools and people. parents of students, activating various religious activities at school, and carrying out active supervision at school. (b) repressive (controlling) strategies, namely writing agreements, summoning parents or guardians of students, and giving sanctions or light punishments. (c) curative (healing) strategy, namely taking a direct approach to students who have problems and emphasizing moral development.